ANALISIS BEBAN KERJA DAN PENENTUAN JUMLAH KARYAWAN DIVISI PRODUKSI DALAM MENYELESAIKAN TARGET DARI PERUSAHAAN - Hardito Novantoro; Mochammad Singgih (LPPM Universitas Bina Bangsa, 2023)
PT. ABC is an industrial company that produces hydrogen peroxide. Hydrogen Peroxide can be used as a bleaching agent in various industries such as paper mills and textile factories. However, PT.ABC still often experiences delays in the process of completing orders so that orders are not on time when the product will be sent to consumers with delays in completing orders that often occur can result in a decrease in consumer confidence in the company, even with these events it can create a great opportunity for competing companies, where consumers will choose to move to competing companies. Where this research raises this problem to seek solutions so that there are no more delays and can meet demand targets. With this problem the problem is formulated how many employees are optimal for completing order requests and also how much workload they receive in doing the work. The purpose of this study is to determine the amount of workload and also determine the optimal number of employees. The method used in this study is Work Sampling and Work Load Analysis (WLA). From the results of calculating the standard time for making hydrogen peroxide, the standard time is 7.13 minutes/unit. from the results of the calculation of the average workload received by employees that is equal to 105.6%. To meet the target customer demand, employees are required to work overtime for 1 hour 8 minutes/day and are given additional overtime incentives, but by increasing their output by 25% of the initial output, so the company does not lose out by providing additional incentives to employees